Influence of non-linear frequency-dependent material properties on the operation of rotating electrical machines. Issue 3 (5th May 2015) - Demenko, Ivo Doležel, Kay Hameyer, Wojciech Pietrowski and Krzysztof Zawirski, Andrzej; Ruf, Andreas; Steentjes, Simon; Franck, David; Hameyer, Kay
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to focus on the frequency-dependent non-linear magnetization behaviour of the soft magnetic material, which influences both the energy loss and the performance of the electrical machine. The applied approach is based on measured material characteristics for various frequencies and magnetic flux densities. These are varied during the simulation according to the operational conditions of the rotating electrical machine. Therewith, the fault being committed neglecting the frequency-dependent magnetization behaviour of the magnetic material is examined in detail. Design/methodology/approach – The influence of non-linear frequency-dependent material properties is studied by variation of the frequency-dependent magnetization characteristics. Two different non-oriented electrical steel grades having the same nominal losses at 1.5 T and 50 Hz, but different thickness, classified as M330-35A and M330-50A are studied in detail. Both have slightly different magnetization and loss behaviour. Findings – This analysis corroborates that it is important to consider the frequency-dependency and saturation behaviour of the ferromagnetic material as well as its magnetic utilization when simulating electrical machines, i.e., its performance. The necessity to change the magnetization curve according to the applied frequency for the calculation of operating points depends on the applied material and the frequency range. Using materials, whose magnetization behaviour is marginally affected by frequency, causes a deviation in the flux-linkage and the electromagnetic torque in a small frequency range. However, analysing larger frequency ranges, the frequency behaviour of the material cannot be neglected. For instance, a poorer magnetizability requires a higher quadrature current to keep the same torque leading to increased copper losses. In addition, the applied iron-loss model plays a central role, since changes in magnetization behaviour with frequency lead to changes in the iron losses. In order to study the impact, the iron-loss model has to be capable to incorporate the harmonic content, because particularly the field harmonics are influenced by the shape of the magnetization curve. Originality/value – This paper gives a close insight on the way the frequency-dependent non-linear magnetization behaviour affects the energy loss and the performance of electrical machines. Therewith measures to tackle this could be derived.